#### Answer

neither

#### Work Step by Step

$6x-y=7 \lt=\gt y=6x-7 =\gt m =6$
$2x+3y=4 \lt=\gt y =-\frac{2}{3}x+\frac{4}{3} =\gt m=-\frac{2}{3}$
$-\frac{2}{3} \times 6 = -4$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

neither

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.